PENGARUH BOLA STANDAR DAN BOLA MODIFIKASI TERHADAP KEMAMPUAN PASSING ATAS DALAM PERMAINAN BOLAVOLI PADA MURID SD INPRES TANGKALA II MAKASSAR - Muhaimin, Ali (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
This Â study Â aims Â toÂ determine; Â (1)Â To Â determine Â the Â extent Â ofÂ the Â effect Â of standard ball size number 4 on the ability of passing on to the elementary Â school students Inpres Tangkala II Makassar. (2) To determine the extent of the effect of modifications to the ball passing ability on the elementary school students Inpres Tangkala II Makassar. Â (3) To find out which is better effect between standard ball ball size number 4 with modifications to the ability of passing on to the elementary Â school students Tangkala II Makassar.Jenis Â this study is the kind of experimentalÂ research. The population is all elementary school students Inpres Tangkala II with a sample of 30 people. Further divided into two groups with ordinal matching Â technique Â is Â to Â group Â standard Â 15 Â ball Â and Â 15 Â ball Â modification.Â Â Sampling technique Â is technique Â saturatedÂ samples. Data analysis technique Â used is the paired t-test and Â unpaired Â t-test. Â Based Â on Â the Â results Â of Â this Â study Â concluded Â that Â (1) Â aÂ significant difference using a standard ball against passing ability on elementary school students Inpres Tangkala Â II Makassar Â City thitung 12.854 and ttabel obtained Â a value of 2.045 (0.000 <Î± 0.05); Â (2) Â a Â significant Â difference Â using Â a Â modificationÂ Â to Â the Â ball Â passing Â ability Â on elementary Â school Â students Â Inpres Â Tangkala Â II of Makassar Â tcount Â = 27 798 and table = 2,045 while the significant value gained 0,000 <Î± 0.05. Due to significant levels of less than 0.05 Î± (3) the use of a modified ball better improve significantly the passing on of the use of standard ball at the elementary school students Inpres Tangkala II Makassar City t = 3,358 and the value table = 2,045, while the value of significant obtained 0.002 <Î± 0:05, because the significance value smaller than Î± 0:05.